2017
DOI: 10.3390/polym9030100
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Property and Cytotoxicity of a Poly(lactic acid)/Nanosilver-Doped Multiwall Carbon Nanotube Nanocomposite

Abstract: A novel method was used to synthesize a nanosilver-doped multiwall carbon nanotube (MWCNT-Ag), and subsequently, the novel poly(lactic acid) (PLA)-and MWCNT-Ag-based biocompatible and antimicrobial nanocomposites were prepared by melt blending. Based on energy dispersive X-ray spectrometry images, an MWCNT-Ag was successfully synthesized. The effect of the MWCNT-Ag on the PLA bionanocomposites was investigated by evaluating their thermal and mechanical properties, antifungal activity, and cytotoxicity. The nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…The nano-TiO 2 could kill microbes because its particle size is very small, and it would generated many electron–hole pairs, which induced redox reactions on those microorganisms [ 49 ]. The antimicrobial mechanism of nano-Ag is that the nano-Ag particle might accumulate in the bacterial cytoplasmic membrane, and the membrane permeability of the bacteria increased significantly, which led to cell death [ 37 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nano-TiO 2 could kill microbes because its particle size is very small, and it would generated many electron–hole pairs, which induced redox reactions on those microorganisms [ 49 ]. The antimicrobial mechanism of nano-Ag is that the nano-Ag particle might accumulate in the bacterial cytoplasmic membrane, and the membrane permeability of the bacteria increased significantly, which led to cell death [ 37 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this concern, the high thermostability of inorganic antimicrobial agents such as metallic nanoscale materials could be incorporated into the food packaging system to extend the shelf life of food and maintain food safety and quality . If the packaging film provides barrier properties to small molecules such as water, CO 2 , and O 2 , they can effectively control the deterioration of agricultural products . One of the most common metallic nanoparticles used in the food packaging industry is nano‐Ag …”
Section: Introductionmentioning
confidence: 99%
“…2,9,10 If the packaging film provides barrier properties to small molecules such as water, CO 2 , and O 2 , they can effectively control the deterioration of agricultural products. 11,12 One of the most common metallic nanoparticles used in the food packaging industry is nano-Ag. [13][14][15][16][17] The PLA/nano-Ag composites had been reported to give improvements in barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lai and Li 21 modified silica by melt blending it with polyurethane to initiate the nucleation of PLA; the crystallization peak temperature and optical transmittance of the modified silica/PLA composite were higher than those of the unmodified silica/PLA composite. Tsou et al 22 synthesized a new nanomaterial (nanosilver-doped multiwall carbon nanotube) to enhance the mechanical property, theromostability, and antibacterial properties of PLA. Moreover, Tsou et al 18 indicated that acetyl tributyl citrate as a plasticizer could enhance the elongation at break of PLA/tapioca composites.…”
Section: Introductionmentioning
confidence: 99%